2018
DOI: 10.1002/ep.12959
|View full text |Cite
|
Sign up to set email alerts
|

N2O absorption through super hydrophobic hollow fiber membrane contactor

Abstract: Dinitrogen monoxide (N2O) is mainly produced in Horticulture and farming activities, industrial processes and combustion of fossil fuels. N2O is one of the harmful emissions and its global warming potential is 310 times greater than CO2 on a molecular basis. This research aims to absorb N2O from its mixture with air through super hydrophobic hollow membrane contactor using a mixture of 0.5M HNO3 and 0.5 wt % H2O2 solutions as absorbent. In the experiment, the feed gas flowed through the shell side of the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Weißbach et al demonstrated a 77% recovery efficiency of N 2 O harvesting from aqueous N 2 O solution using an SGMC process, along with a potential recovery efficiency of up to 90% . VGMs in a hollow fiber module were also recently applied to separate N 2 O from its mixture with air …”
Section: Recovery Of Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weißbach et al demonstrated a 77% recovery efficiency of N 2 O harvesting from aqueous N 2 O solution using an SGMC process, along with a potential recovery efficiency of up to 90% . VGMs in a hollow fiber module were also recently applied to separate N 2 O from its mixture with air …”
Section: Recovery Of Volatile Compoundsmentioning
confidence: 99%
“…156 VGMs in a hollow fiber module were also recently applied to separate N 2 O from its mixture with air. 157 While the high solubility of N 2 O in water slows down the recovery process, the large membrane areas available in hollow fiber modules can readily compensate for the recovery rate. However, as the energy potential is relatively low, highstrength wastewater would be required as a proper source of N 2 O.…”
Section: Acs Esandt Engineeringmentioning
confidence: 99%